Orodispersible Tablets of Carbamazepine Prepared by Direct Compression Method Using 32 Full Factorial Design (Dhaka University Journal of Pharmaceutical Sciences, 2008)
Orodispersible tablets of carbamazepine were prepared with a view to enhance patient compliance by direct compression method using 3² full factorial design. Crospovidone (2-10% w/w) was used as superdisintegrant and microcrystallinecellulose (0-30% w/w) was used as diluent, along with directly compressible mannitol to enhance mouth feel. The tablets were evaluated for hardness, friability, thickness, drug content uniformity, in vitro dispersion time, wetting time and water absorption ratio. Based on in vitro dispersion time (approximately 10 s); the formulation containing 2% w/w crospovidone and 30%w/w microcrystallinecellulose was found to be promising and tested for in vitro drug release pattern (in pH 6.8 phosphate buffer), short-term stability (at 40º/75 % RH for 3 w) and drug-excipient interaction. This formulation showed four-fold faster drug release (t25%) compared to the conventional commercial tablet formulation. Short-term stability studies on the formulation indicated that there are no significant changes in drug content and in vitro dispersion time (p < 0.05).Key words: Orodispersible tablets, carbamazepine, crospovidone, micro crystallinecellulose, 3² full factorial designDOI = 10.3329/dujps.v7i1.1199Dhaka Univ. J. Pharm. Sci. 7(1): 1-5, 2008 (June)